The violence of the biblical God: canonical narrative and Christian faith - Hawk, L. Daniel (William B. Eerdmans Publishing Company, 2019)
The problem of the violent God -- Creation ruined and remade -- Yahweh's new approach -- The grand entrance -- A covenant made and remade -- God and kings -- The land promised and taken -- God moves to the outside -- Interpreting divine violence